Safety concerns over biomedical waste management in a tertiary care centre of North Kerala - Rose Jacob, Sabitha; Bhaskar, Anitha; Varkey George, Rony; G, Harikrishnan (Public Health Review: International Journal of Public Health Research, 2017)
Introduction: Exposure to infected body fluids and contact with contaminated materials while handling bio medical waste make health workers at high risk for blood borne infections. Objective: To assess safety precaution profile and biomedical waste management practices among different categories of health staff. Materials and methods: A cross sectional study was conducted among 141 health care personnel of a tertiary care center on single shift of a day using a structured pre- tested interview schedule. Data were analyzed using SPSS 16 trial version. Results: The study population included 25(17.6%) doctors, 59(41.5%) nurses, 14(9.9%) nursing assistants, 19(13.4%)hospital attendants and 13(9.2%) lab technicians and 11(7.8%) other daily wage cleaning staff involved in waste management. 104 (73.8%)were females. 91(64.5%)were permanent staff while 50 were on contract. 121(89.4%) had work experience more than 1year.71(50.4%)received no training on bio medical waste management and 18 (12.8%) had training within 6 months. Only 74(52.1%) were fully immunized against Hepatitis B with a significantly less coverage among nursing assistants and hospital attendants (p=.000). 60(42.6%)had sharp injury male sex (p=.042), being in category of nursing assistants (p=.000), permanent job status (p=.000) and experience more than 5 years in absence of training (p=.010) were risk factors significantly associated with sharp injury.101(72.3%) always segregated waste as per categories and 110(78% ) always used gloves while handling it. Conclusions: Around half of the health personnel are not following safety practices and sustained sharp injuries while handling biomedical waste. Only half of the health personnel were immunized against Hepatitis B.